Flexible Magnetoreceptor with Tunable Intrinsic Logic for On‐Skin Touchless Human‐Machine Interfaces. (26th March 2021) - Makushko, Pavlo; Oliveros Mata, Eduardo Sergio; Cañón Bermúdez, Gilbert Santiago; Hassan, Mariam; Laureti, Sara; Rinaldi, Christian; Fagiani, Federico; Barucca, Gianni; Schmidt, Nataliia; Zabila, Yevhen; Kosub, Tobias; Illing, Rico; et al.
Abstract: Artificial magnetoception is a new and yet to be explored path for humans to interact with the surroundings. This technology is enabled by thin film magnetic field sensors embedded in a soft and flexible format to constitute magnetosensitive electronic skins (e‐skins). Being limited by the sensitivity to in‐plane magnetic fields, magnetosensitive e‐skins are restricted to basic proximity and angle sensing and are not used as switches or logic elements of interactive wearable electronics. Here, a novel magnetoreceptive platform for on‐skin touchless interactive electronics based on flexible spin valve switches with sensitivity to out‐of‐plane magnetic fields is demonstrated. The technology relies on all‐metal Co/Pd‐based spin valves with a synthetic antiferromagnet possessing perpendicular magnetic anisotropy. The flexible magnetoreceptors act as logic elements, namely momentary and permanent (latching) switches. The switches maintain their performance even upon bending to a radius of less than 3.5 mm and withstand repetitive bending for hundreds of cycles. Here, flexible switches are integrated in on‐skin interactive electronics and their performance as touchless human‐machine interfaces is demonstrated, which are intuitive to use, energy efficient, and insensitive to external magnetic disturbances. This technology offers qualitatively new functionalities for electronic skins and paves the way towards full‐fledged on‐skin touchless interactive electronics. Abstract : Artificial magnetoception, that is, electronically expanding human perception to detect magnetic fields, is a new and yet unexplored route for interacting with the surroundings. Here, skin‐compliant touchless interactive devices based on spin‐valves with out‐of‐plane sensitivity to magnetic fields are presented. These devices reveal tunable logic characteristics, as needed for intuitive, energy efficient, and insensitive to magnetic disturbances magnetoreceptive human‐machine interfaces.